A viagem como produção da diferença : deslocamento e territorialidade entre o povo Wauja, Alto Xingu - Amaro, Fernanda Ribeiro, 1985- (2020)
Orientadores: Carlos Rodrigues Brandão, Antonio Roberto Guerreiro Junior (1984)